Examining risk and protective factors for psychological health during the COVID-19 pandemic. Issue 1 (2nd January 2022) - Racine, Sarah; Miller, Alexia; Mehak, Adrienne; Trolio, Vittoria
ABSTRACT: Background and Objectives: The coronavirus disease 2019 (COVID-19) pandemic has profoundly impacted people's lives, with significant mental health consequences emerging. In addition to sociodemographic and COVID-19 specific factors, psychological risk and protective mechanisms likely influence individual differences in mental health during the COVID-19 pandemic. We examined associations between a broad set of risk and protective factors with depression, anxiety, alcohol problems, and eating pathology, and investigated interactions between objective stress due to COVID-19 and risk/protective variables in predicting psychopathology. Methods: Participants were 877 adults (73.7% female) recruited via internet sources from around the globe, but primarily residing in North America (87.4%). Results: Structural equation modelling revealed that certain risk and protective factors (e.g., loneliness, mindfulness) were broadly related to psychopathology, whereas others showed unique relations with specific symptoms (e.g., greater repetitive thinking and anxiety; low meaning and purpose and depression). COVID-19 objective stress interacted with risk factors, but not protective factors, to predict greater anxiety symptoms, but not other forms of psychopathology. Conclusions: Findings contribute to our understanding of psychological mechanisms underlying individual differences in psychopathology in the context of a global stressor. Strategies that reduce loneliness and increase mindfulness will likely impact the greatest number of mental health symptoms.